High Surface Area Contorted Conjugated Microporous Polymers Based on Spiro-Bipropylenedioxythiophene - Jiang, Jia-Xing; Laybourn, Andrea; Clowes, Rob; Khimyak, Yaroslav Z; Bacsa, John; Higgins, Simon J; Adams, Dave J; Cooper, Andrew I (Macromolecules, 2010)
Conjugated polymers derived from thiophene or 3,4-ethylenedioxythiophene derivatives have been widely investigated for use in organic thin-film transistors and organic photovoltaic devices. We describe here the synthesis of a series of conjugated microporous polymers formed by reaction of spiro-bis(2,5-dibromopropylenedioxythiophene) with one of three di- or triethynyl monomers. These polymers have surface areas up to 1631 m2/g and exhibit significant microporosity, suggesting possible applications in the fields of organic electronics or optoelectronics.